1973
DOI: 10.1128/iai.8.5.796-803.1973
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma-Associated Induction of Interferon in Ovine Leukocytes

Abstract: A mycoplasmal species, Acholeplasma laidlawii, isolated as a contaminant from a fetal lamb kidney cell line, was shown to be associated with the induction of interferon in cultures of ovine peripheral blood leukocytes. Broth cultures of the mycoplasma induced between 20 and 230 U of interferon per ml in leukocytes from two adult ewes. The amount of interferon produced correlated with the inoculum size of mycoplasma. Interferon production was associated with replication of the mycoplasma in the leukocyte cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…It has been shown that mycoplasmas induce IFN and other lymphokines productions by human, animal lymphocytes and their established cell lines (10,24). We reported previously that IFN was produced by human peripheral lymphocytes stimulated by Al.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been shown that mycoplasmas induce IFN and other lymphokines productions by human, animal lymphocytes and their established cell lines (10,24). We reported previously that IFN was produced by human peripheral lymphocytes stimulated by Al.…”
Section: Discussionmentioning
confidence: 86%
“…These microorganisms lack the specific cell wall components of bacteria, such as diaminopimelic and muramic acids, and exist predominantly in an extracellular environment in close association with the cell plasma membrane (5). Although mycoplasmas can cause minimal morphological changes in mycoplasma-infected cell cultures, the possible simultaneous effects are numerous, in mycoplasma-infected immunocytes, such as lymphocytes, macrophages, and hybridoma cell lines, including enhancement of productions of immunoglobulin (26), cytokines (23), and interferon (4,10,24). Furthermore, the cytotoxicity of macrophages (17,20) and natural killer (NK) cells (7,18) to target cells are enhanced, when these cell lines were contaminated with mycoplasmas.…”
mentioning
confidence: 99%
“…Eleven other species of mycoplasmas were also capable of Inducing inter feron production in ovine leukocyte cultures (70). Live organisms were required for interferon production to occur (25,70).…”
Section: Induction Of Interferon Productionmentioning
confidence: 99%
“…The first successful ^ vitro Induction of Interferon production by mycoplasmas was obtained ^en ovine leukocytes growing in mixed culture with fetal lamb kidney cells produced substantial levels of Interferon, which were attributed to infection of the kidney cells by A. laldlawii (25).…”
Section: Induction Of Interferon Productionmentioning
confidence: 99%
“…Initial attempts to demonstrate interferon induction by mycoplasmas failed when chicken embryo cells (22,27), mouse L cells (2), hamster embryo fibroblasts (21), and human embryonic kidney cells (2) were used. Recently we demonstrated that ovine leukocytes but not fetal lamb kidney cells produced interferon in response to a variety of mycoplasma species (19,20). Although interferon has not been detected in mouse reticuloendothelial cells exposed to mycoplasmas in vitro (18), mouse interferon has been demonstrated in vivo after intravenous (J. S. Youngner and W. R. Stinebring, personal communication) or intraperitoneal (8,18) injection of the organisms.…”
mentioning
confidence: 99%